THE DEVELOPMENT OF COMICS FOR PHYSICS LEARNING BASED ON GRAPHIC DESIGN FOR JUNIOR HIGH SCHOOL STUDENTS - Hendri Noperi; Kartini Herlina; Agus Suyatna (Universitas Nahdlatul Ulama Lampung, 2018)
Based on observations made to physics teachers and students at the Junior High School (SMP) 7 Bandar Lampung and SMP PGRI I BumiAgung, it is known that the physics learning process undertaken by teachers often does not teach physics applications in students’ lives. In addition, print-based learning media at this time are also verbalistic and have not been able to link physics with life around students. The learning process and the lack of media that can link theory and application in student life make students feel bored studying physics. Physics learning comics are media that are able to link the concepts of physics with life around students. This condition is the background of conducting research, developing physics learning comics as supplement media which are thought to be interesting and effective for students. This research is a research and development (R&D) of comics for based on graphic design that aims to describe the characteristics of Physics Learning Comics. Research and development of comics for physics learning is carried out by following procedures (1) needs analysis, (2) making goals, (3) determining the subject matter, (4) synopsis writing (5) initial script writing, (6) prototype production, (7) evaluation, (8) revision, (9) final script writing, (10) trials and (11) final comics. The results of tests with operational tests show that 84.21% of students can pass the KKM SMP N 7 Bandar Lampung and the results of the attractiveness test taken from a questionnaire score of 3.51 indicate that this comic of physics learning is effective and very interesting to learn. Keywords: research and development,physics comic, graphic design,